Domestic fortress : Fear and the new home front - Atkinson, Rowland; Blandy, Sarah (Book collections on Project MUSE., 2016)
Using a rich range of sources from cutting-edge research to media accounts, Domestic Fortress considers the fantasies and realities of dangers to the contemporary home and its inhabitants and details the extreme measures now used in the pursuit of total safety.